Eksperimental Study the Effect of Additional Flat Plate Reflector to Performance the Sinusoidal Solar Water Heater - Dedy Ashari; Djatmiko Ichsani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
New Renewable Energy is currently not fully utilized. Energy sourced from the sun is one of the most exploited energy sources today in several countries in the world, which in large scale has been used as a power plant. The solar collector is a heat exchange device that serves to convert solar radiation energy into a form of heat energy to heat a working fluid, such as water and air. Various methods have been undertaken to improve the performance of solar collectors, including using flat plate reflectors. Reflectors are used to reflect the diffused sunlight to focus on solar cells and ultimately increase the value of solar cell output power. Experimental studies in this study were conducted to see the performance of a solar collector sinusoidal with and without the addition of reflectors under varying discharge conditions. Variations of mass flow rate in this study were 18 and 20 liters/hour. The reflector angle on the solar collector is set at 40° on both sides of the reflector. From this study, the results for the efficiency of a solar collector with the addition of a reflector are the highest at 43,91% at a mass flow rate of 20 liters / hour.